2006
DOI: 10.1088/0031-9155/51/20/001
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic response of compliable microvessels containing ultrasound contrast agents

Abstract: The existing models of the dynamics of ultrasound contrast agents (UCAs) have largely been focused on an UCA surrounded by an infinite liquid. Preliminary investigations of a microbubble's oscillation in a rigid tube have been performed using linear perturbation, under the assumption that the tube diameter is significantly larger than UCA size. In the potential application of drug and gene delivery, it may be desirable to fragment the agent shell within small blood vessels and in some cases to rupture the vess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
91
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 43 publications
7
91
0
1
Order By: Relevance
“…Previously, the vascular damage was attributed to either the vessel distension or direct impact of a bubble jet on a vessel wall. [10][11][12] However, recent high speed photographs of ex vivo vessels showed that the bubble collapse within a vessel generates a distinct invagination of the vessel wall (i.e., toward the lumen of the vessel). 13,14 This bubble-vessel coupling may be responsible for some vascular damage.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the vascular damage was attributed to either the vessel distension or direct impact of a bubble jet on a vessel wall. [10][11][12] However, recent high speed photographs of ex vivo vessels showed that the bubble collapse within a vessel generates a distinct invagination of the vessel wall (i.e., toward the lumen of the vessel). 13,14 This bubble-vessel coupling may be responsible for some vascular damage.…”
Section: Introductionmentioning
confidence: 99%
“…This bioeffect is readily observable, of clear biological significance and serves as the threshold of concern for patient risk. While the modeling of specific mechanisms of capillary injury, such as capillary stretching (Qin and Ferrara, 2006;Miao et al 2008), vessel invagination (Hosseinkhah et al 2013), jet impingement (Chen et al 2011), and fluid stress (Hosseinkhah et al 2015), and possibly others, is an ultimate goal, such modeling likely would require extensive detailed theoretical analysis by three-dimensional finite-amplitude methods for any full accounting of the complex microbubble-capillary problem. Here, we pursue the general approach of the MI which was based primarily on theoretical microbubble behavior in an effort to obtain general insights into the problem.…”
Section: Introductionmentioning
confidence: 99%
“…Finite volume and finite element models of a bubble in a compliant tube have recently been developed to investigate the interaction of an ultrasonically excited bubble and a microvessel (Gao et al, 2007;Qin and Ferrara, 2006;Qin et al, 2006;. These models were used to predict the amplitude and asymmetry of bubble response and the stresses on the tube wall.…”
Section: Introductionmentioning
confidence: 99%